Issues relating to Islamic Bank's adaption to fintech - Saleh, Abdulmajid Obaid Hasan; Mizna Adnan Alqaderi, Mizna Adnan Alqaderi (2022)
Fintech, or financial technology, is a new type of financial transaction technology. It is a disruptive technology that will alter stakeholders' banking behaviour. It refers to several financial transactions that take place without the assistance of a person, including money transfers, depositing a check with your smartphone, skipping a bank office to apply for credit, raising funds for a business beginning, or managing your investments. The growing rise of Fintech affects not only the traditional finance industry but also the Islamic finance industry since the Islamic finance sector embraces Fintech as part of the financial revolution. As a result, Islamic Fintech or Shariah-compliant Fintech enters the picture for people who are concerned about questions of faith and religion when it comes to banking. In this paper, the recent development of Islamic Fintech in Malaysia and issues related to fintech adoption by banks are discussed.